Aesthetic appreciation: event-related field and time-frequency analyses - Munar, Enric; Nadal, Marcos; Castellanos, Nazareth P.; Flexas, Albert; Maestú, Fernando; Mirasso, Claudio; Cela-Conde, Camilo J. (Frontiers in Human Neuroscience, 2012)
Improvements in neuroimaging methods have afforded significant advances in our knowledge of the cognitive and neural foundations of aesthetic appreciation. We used magnetoencephalography (MEG) to register brain activity while participants decided about the beauty of visual stimuli. The data were analyzed with event-related field (ERF) and Time-Frequency (TF) procedures. ERFs revealed no significant differences between brain activity related with stimuli rated as “beautiful” and “not beautiful.” TF analysis showed clear differences between both conditions 400 ms after stimulus onset. Oscillatory power was greater for stimuli rated as “beautiful” than those regarded as “not beautiful” in the four frequency bands (theta, alpha, beta, and gamma). These results are interpreted in the frame of synchronization studies.